The monkey and the wrench : essays into contemporary poetics - Biddinger, Mary; Gallaher, John, 1965- (Akron series in contemporary poetics, 2011)
The Monkey and the Wrench: Essays into Contemporary Poetics takes a snapshot of a moving target: the ever-shifting conversation about today's poetry. The ten essays in this collection offer reflections and insights, practical advice for craft matters, and provocative points of departure for those who read and write poetry. This series seeks to further the discussion of poetics in America and beyond, and to showcase the ideas of writers and critics with varied sensibilities. The first volume in the Akron Series in Contemporary Poetics, The Monkey & the Wrench, explores the debate over hybrid aesthetics, confronts the topic of contemporary rhyme, and ventures into the realm of persona and the mystical poem. This volume is ideal for both the classroom and the nightstand, for the poet's desk and the critic's bookshelf. Series editors Mary Biddinger and John Gallaher have assembled an eclectic collection that welcomes the reader into the conversation, while documenting the seismic activity of today's poetry world.